Hadith #2451 - Sunan Abi Dawud - al-Hasan bin 'Ubaidullah الحسن بن عبيد الله بن عروة; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
The apostle of Allah (ﷺ) used to fast three days every month: Monday, Thursday and Monday in the next week.
Grade: Hasan

Hadith #3250 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Hasan bin 'Ubaidullah الحسن بن عبيد الله بن عروة; Sa'd bin 'Ubaida al-Salmi سعد بن عبيدة السلمي أبو حمزة (Sunan Abi Dawud)
” ‘Umar said: I swear by Allah, I never swore by it personally or reporting it from others.”
Grade: Sahih

Hadith #5069 - Sunan Abi Dawud - Abdur Rahman bin Yazid bin Jabir عبد الرحمن بن يزيد بن جابر الأزدي; al-Hasan bin 'Ubaidullah الحسن بن عبيد الله بن عروة; ibn Umar; Ibrahim bin Suwayd al-Nkh'y إبراهيم بن سويد النخعي; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin Qdamh bin A'yn محمد بن قدامة بن أعين; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone says in the morning or in the evening: “O Allah! in the morning we call Thee, the bearers of Thy Throne, Thy angels and all Thy creatures to witness that thou art Allah (God) than Whom alone there is no god, and that Muhammad is Thy Servant and Apostle,” Allah will emancipate his fourth from Hell; if anyone says twice, Allah will emancipate his half; if anyone says it thrice, Allah will emancipate three-fourth; and if he says four times, Allah will emancipa
Grade: Hasan